Rerouting spare part distribution on pt tam spld with nearest neighbor method - Jusup, Ravi Prianka; Muttaqin, Zaenal; Sukmadewi, Rani (Institute of Computer Science (IOCS), 2024)
This article presents a study conducted at PT Toyota Astra Motor Spare Parts Logistics Division (SPLD) focusing on improving the rerouting process for spare part distribution to ten part shops in Cikarang and Karawang City. Utilizing the nearest neighbor algorithm, the researcher aimed to devise an efficient route originating from the Centre Warehouse in Kawasan Industri MM 2100. The primary objectives were to minimize distance traveled and consolidate routes to achieve cost savings in transportation. Through meticulous route planning and optimization, the study successfully reduced the total distance from 282 km to 62.8 km, thereby demonstrating significant cost-saving potential. This article provides insights into the methodology, results, and implications of implementing the nearest neighbor algorithm in optimizing spare part distribution logistics for automotive industries